Compressão de Sequências de Imagens com Alta Qualidade e Baixa Taxa de Bits DOI: 10.14209/jcis.1995.6 - V. Lamar, M.; C. M. Bermudez, J.; Seara, R. (Journal of Communication and Information Systems, 2015)
This paper presents a new video coding structure for application in videophone and videoconferencing systems. The new structure utilizes image segmentation by quadtree decomposition in the motion estimation and compensation stages. A significant reduction in computational effort is achieved, as compared to conventional structure. The new scheme leads to a high objective image quality for operation at low bit rates. Computer simulations are presented which compare the new structure and a coder based on the H.261 standard for performance. The results obtained demonstrate the effectiveness of the new coding scheme.